Predicting career adaptability through individual factors and moderating role of social support among junior employees in Malaysia - Anas, Ilyana (2022)
In this 21st century, job prospects worldwide are impacted by various challenges such as globalisation, and technological advancement. On the other hand, challenges such as unemployment, transition from school to work, skill mismatched, and pandemic, have fundamentally changed economic policies and global trade activities, especially in terms of human capital. Career adaptability is, without doubt, an indispensable asset, helping the individual forge ahead regardless of numerous challenges at the workplace. Therefore, with the support of System Theory Framework of Career Development (STFCD), Life-span and Life-Space Theory, and Career Construction Theory (CCT), this research sought to determine the contribution of individual factors towards career adaptability among junior employees who had been employed for less than two years. This cohort is considered as entry-level employees in organisations. Several dimensions of individual factors focused on this research were self-esteem, conscientiousness, spiritual intelligence, and social support. Quantitative approach using a cross-sectional survey was employed and the questionnaire was distributed to the sample comprised junior employees (n=423) graduated from four Malaysian public universities. SPSS and SEM AMOS were used to analyse the data. The results suggested that the self-esteem and conscientiousness have significant contribution on career adaptability. Contrary to what has been assumed, spiritual intelligence and social support showed nonsignificant result. In this cohort, social support has moderating role on selfesteem and career adaptability. Therefore, the research conclude that selfesteem and conscientiousness are the principal factors predicting career adaptability and social support moderate the association between self-esteem and career adaptability. The research provides valuable information to stakeholders especially employers and higher education institution in managing individuals.